ESC Working Group Cellular Biology of the Heart: Position Paper: improving the preclinical assessment of novel cardioprotective therapies - Lecour, Sandrine; Botker, Hans E.; Condorelli, Gianluigi; Davidson, Sean M.; Garcia-Dorado, David; Engel, Felix; Ferdinandy, Peter; Heusch, Gerd; Madonna, Rosalinda; Ovize, Michel; Ruiz-Meana, Marisol; Schulz, Rainer; et al. (Cardiovascular Research, 2014)
Ischaemic heart disease (IHD) remains the leading cause of death and disability worldwide. As a result, novel therapies are still needed to protect the heart from the detrimental effects of acute ischaemia-reperfusion injury, in order to improve clinical outcomes in IHD patients. In this regard, although a large number of novel cardioprotective therapies discovered in the research laboratory have been investigated in the clinical setting, only a few of these have been demonstrated to improve clinical outcomes. One potential reason for this lack of success may have been the failure to thoroughly assess the cardioprotective efficacy of these novel therapies in suitably designed preclinical experimental animal models. Therefore, the aim of this Position Paper by the European Society of Cardiology Working Group Cellular Biology of the Heart is to provide recommendations for improving the preclinical assessment of novel cardioprotective therapies discovered in the research laboratory, with the aim of increasing the likelihood of success in translating these new treatments into improved clinical outcomes.
EVALuna2:25478